Fracture of Cobalt-Crome Modular Neck in Total Hip Arthroplasty - Murena, Luigi; Maritan, Guido; Concina, Chiara; Scamacca, Veronica; Ratti, Chiara; Canton, Gianluca (Acta Biomedica Atenei Parmensis, 2019)
Despite the advantages of modular total hip arthroplasty in terms of neck version, offset and length precise reproduction, titanium necks breakage became a concern. Consequently, titanium has been replaced by cobalt-chrome (Co-Cr). However, four cases of Co-Cr modular neck breakage have been reported in the literature. In the present paper, two cases of Co-Cr modular neck fractures are described together with a literature review. The aim of this work is to discuss the risk factors and characteristics of this rare complication. We described two cases of fracture of long varus Co-Cr modular femoral neck connected with cementless press-fit stem. Some risk factors, such as long varus type of modular neck, overweight and/or high demanding physical activity, might have contributed to implant failure.